LIQUEFACTION PHENOMENA TRIGGERED BY THE EARTHQUAKE OF AUGUST 14,2003, IN THE ISLAND OF LEFKADA, GREECE - Παπαθανασίου, Γ.; Παυλίδης, Σπ.; Χρηστάρας, B.; Πιτιλάκης, K. (Bulletin of the Geological Society of Greece, 2004)
In the early morning of August 14, 2003 (05:14:53.9 GMT; 08:14:54 local time), a strong (Ms=6.4, Mw=6.2, a=0.42g) damaging earthquake occurred offshore the NW coast of Lefkada Island (Ionian, Greece). According to the Seismological laboratory of Aristotle University Of Thessaloniki, its focus was located at 38.86 N, 20.73 E (fig. 1 ) at depth h = 10km. Extensive ground failures (rock falls, liquefaction, cracks) were observed. The maximum intensity has been evaluated lo = Vili (EMS) at Lefkas municipality. Historical evidence of liquefaction show that the island suffered from similar co-seismic effects from past earthquakes, especially from 1914 and 1948 shocks. From the liquefaction sites, representing samples of the ejected soil were examined with a view to evaluate the liquefaction susceptibility of them. The results of the laboratory tests show that according to the Chinese Criteria (Wang 1979) these soils are considered to be of high potentially liquéfiable type.